Alteration of the phenology of leaf senescence and fall in winter deciduous species by climate change: effects on nutrient proficiency - Estiarte, Marc; Peñuelas, Josep (Global change biology, 2015)
Leaf senescence in winter deciduous species signals the transition from the active to the dormant stage. The purpose of leaf senescence is the recovery of nutrients before the leaves fall. Photoperiod and temperature are the main cues controlling leaf senescence in winter deciduous species, with water stress imposing an additional influence. Photoperiod exerts a strict control on leaf senescence at latitudes where winters are severe and temperature gains importance in the regulation as winters become less severe. On average, climatic warming will delay and drought will advance leaf senescence, but at varying degrees depending on the species. Warming and drought thus have opposite effects on the phenology of leaf senescence, and the impact of climate change will therefore depend on the relative importance of each factor in specific regions. Warming is not expected to have a strong impact on nutrient proficiency although a slower speed of leaf senescence induced by warming could facilitate a more efficient nutrient resorption. Nutrient resorption is less efficient when the leaves senesce prematurely as a consequence of water stress. The overall effects of climate change on nutrient resorption will depend on the contrasting effects of warming and drought. Changes in nutrient resorption and proficiency will impact production in the following year, at least in early spring, because the construction of new foliage relies almost exclusively on nutrients resorbed from foliage during the preceding leaf fall. Changes in the phenology of leaf senescence will thus impact carbon uptake, but also ecosystem nutrient cycling, especially if the changes are consequence of water stress.